New and future developments in microbial biotechnology and bioengineering : trends of microbial biotechnology for sustainable agriculture and biomedicine systems,: trends of microbial biotechnology for sustainable agriculture and biomedicine systems,. Perspectives for human health / (2020) - Unknown
No abstract available